Teaching wildlife techniques to millennials with a flipped classroom. (6th November 2015) - McCleery, Robert
ABSTRACT: Millennials prefer to learn by working in groups, using technology, engaging in real‐world issues, and discussing course content. To accommodate and engage these learning preferences, I modified the traditional Wildlife Techniques lecture and lab structure by "flipping" the class. I placed lectures and instructional videos online and used class time for discussion and problem‐solving. Evaluating students' perceptions of this approach revealed that they clearly found discussion groups helpful and preferred them to the traditional lectures used in other classes. Students did not have a clear preference between online versus in‐class lectures. However, placing lectures online provided students with the opportunity to have discussion groups during regularly scheduled class time. Students generally felt that discussion groups helped them to understand the lectures, whereas the videos allowed them to use their time efficiently. Students reported that this course increased their knowledge of the targeted subject. In total, the flipped class approach appears to engage the millennial student in wildlife sciences in a format that accommodates their learning preferences. © 2015 The Wildlife Society.